Voicesetting: Voice Authoring UIs for Improved Expressivity in Augmentative Communication - Fiannaca, Alex; Paradiso, Ann; Campbell, Jon; Morris, Meredith Ringel (2018 ACM Conference on Human Factors in Computing Systems (CHI), 2018)
Alternative and augmentative communication (AAC) systems used by people with speech disabilities rely on text-to-speech (TTS) engines for synthesizing speech. Advances in TTS systems allowing for the rendering of speech with a range of emotions have yet to be incorporated into AAC systems, leaving AAC users with speech that is mostly devoid of emotion and expressivity. In this work, we describe voicesetting as the process of authoring the speech properties of text. We present the design and evaluation of two voicesetting user interfaces: the Expressive Keyboard, designed for rapid addition of expressivity to speech, and the Voicesetting Editor, designed for more careful crafting of the way text should be spoken. We evaluated the perceived output quality, requisite effort, and usability of both interfaces; the concept of voicesetting and our interfaces were highly valued by end-users as an enhancement to communication quality. We close by discussing design insights from our evaluations.